The functional neuroanatomy of pleasure and happiness. - Kringelbach, M; Berridge, K (2010)
Over fifty years ago the discovery that rats would work to electrically stimulate their brains suggested the intriguing possibility that bliss could be achieved through the use of 'pleasure electrodes' implanted deep within the brain. Subsequent research has failed to bring about this brave new world of boundless pleasure, but more recent findings have started to throw new light on the intriguing links between brain mechanisms of pleasure and happiness. We discuss these findings of the underlying neural mechanisms and functional neuroanatomy of pleasure in the brain. In particular we address how they may come to shed light on our understanding of the brain basis of happiness. Beyond sensory pleasures, we examine how higher pleasures may be related to the brain's default networks, especially in orchestrating cognitive aspects of the meaningfulness important to happiness. We also address how understanding of the hedonic brain might help alleviate the suffering caused by the lack of pleasure, anhedonia, which is a central feature of affective disorders such as depression and chronic pain.